Peran Dinas Sosial dalam Penyelenggaraan Hak Kesejahteraan Sosial Bagi Penyandang Disabilitas di Kecamatan Pangkalan Kerinci Kabupaten Pelalawan - Permata Pangestuti, Bhella; Rahmah, Sitti (Policy, Law and Political Research Center, 2025)
The role of the Social Service is important to ensure the welfare of persons with disabilities. People with disabilities must be supported by getting welfare rights. This study aims to determine the extent of the role of social services in the implementation of social welfare rights for persons with disabilities in Pangkalan Kerinci District, Pelalawan Regency. This research uses a qualitative descriptive method. The research location is at the Social Service of Pelalawan Regency. Determination of informants is done by means of proposive sampling. Data collection by interview, observation and documentation. The results showed that the Pelalawan Regency Social Service has tried to carry out its role in the implementation of social welfare rights for persons with disabilities in Pangkalan Kerinci District, but it has not been done optimally. The inhibiting factors are the lack of effective information provision, the process of distributing disability equipment assistance, limited funds, and lack of awareness from some people with disabilities. The need for increased socialization, social rehabilitation and cooperation with outside agencies by the Pelalawan Regency Social Service.